Practical design of magnetostatic structure using numerical simulation - Wang, Qiuliang (John Wiley & Sons Inc., 2013)
"Covers extensively the magnet design and computation aspects from theories to practical applications, emphasizing design methods of practical structures such as superconducting, electromagnetic and permanent magnet for use in various scientific instruments, industrial processing, biomedicine and special electrical equipments"--